IDENTIFIKASI NILAI-NILAI ARSITEKTUR DAN HISTORIS SEKOLAH CHANG HWA DI KABUPATEN DONGGALA SEBAGAI UPAYA PELESTARIAN BANGUNAN BERSEJARAH (Jurnal Arsitektur ARCADE, 2026)
Chang Hwa School in Donggala Regency is one of the historical buildings that reflects the acculturation of Chinese and Dutch colonial architecture. This study aims to identify the architectural and historical values contained in the building as a basis for preservation efforts. The method used is a qualitative descriptive approach through field studies, visual observations, and interviews with local sources. The results of the study show that the building has distinctive characteristics such as symmetrical structures, chinese-style decorative elements, and the use of local materials that are appropriate for the tropical climate. From a historical perspective, this school is a symbol of the role of the chinese community in education during the colonial period. Identification of these values emphasizes the importance of preserving the building through an adaptive approach without eliminating its architectural authenticity. This study recommends formal protection measures and educational utilization so that the existence of Chang Hwa School continues to contribute to local cultural identity
Keywords: colonial architecture, historical value, preservation, Chang Hwa School, Donggala.